Evaluation of Dietary Turmeric (Curcuma longa) As a Reproductive Modulator in Nile Tilapia (Oreochromis niloticus): An Exploratory Study on Its Contraceptive Properties - Nduoyo, Jane E.; Ekwu, Alice O.; Umanah, Saviour I.; Udo, Imefon U.; Akpan, Imekan I. (Aceh Journal of Animal Science, 2025)
Prolific breeding often hinders tilapia culture, leading to stunted growth and small-sized individuals at harvest. Phyto-additives, such as Turmeric Meal (TM), have been explored as a means of inducing infertility in aquaculture. This study investigated the efficacy of Turmeric Meal (TM) in regulating reproductive parameters and inducing infertility in Nile tilapia. We divided five hundred and forty tilapia into six treatment groups and three replicates, using TMT1 as the control. The remaining groups received diets containing 3%, 4%, 5%, 6%, and 7% TM for 126 days. Results showed no significant differences in growth performance, feed utilization, or survival rate among treatments. However, significant reductions in reproductive parameters, except for absolute and relative fecundity, were observed. Histological analysis revealed reduced fertility in female fish fed from TMT2 through TMT6, while male fish fed TMT4 exhibited signs of infertility. Sperm quality parameters, including motility and morphology, also indicated decreased fertility. The findings suggest that turmeric meal at concentrations of 3-7% can induce infertility in both male and female Nile tilapia when administered over an extended period.